IMPROVING THE MECHANICAL PROPERTIES OF CK35 STEEL USING ND: YAG LASER SURFACE HARDENING - Dawood Salman, Khansaa; Zedain Khalifa, Muhannad (Journal of Engineering and Sustainable Development, 2016)
In this investigation CK35 steel was treated by using laser surface treatment and make comparison with conventionally heat treatment. Laser hardening was done by using pulse ND: YAG laser with energy of 1000mj, whilst the conventionally heat treatment was carried out by quenching at 840 with cooling in oil and then tempered at 200for 2hr. Mechanical tests were made for all the specimens which were used in this research before and after heat treatments such as: Tensile test and Microhardness test. Also grain size measurement and microstructural evaluation were done by using computerized optical microscopy. The results of this work showed that obviously improvement in mechanical properties for the specimen treated by laser more than the specimen treated conventionally as the following: From tensile test it showed that increasing in yield strength, ultimate tensile strength, elongation percentage and plasticity constant (k). Also decreasing in young modulus (E) and the coefficient of strain hardening (n). Whilst the microhardness results showed that the highest value was obtained by laser hardening at the surface of the specimen and deceased far from the surface with depth of hardening equal to 0.5 mm. Also metallographic examination of the specimens after heat treatments showed that refining in grain size of the specimen treated by laser treatment more than the specimen treated by conventional heat treatment.